Hepatitis C virus infection in end‐stage renal disease and kidney transplantation. (19th June 2014) - Burra, Patrizia; Rodríguez‐Castro, Kryssia I.; Marchini, Francesco; Bonfante, Luciana; Furian, Lucrezia; Ferrarese, Alberto; Zanetto, Alberto; Germani, Giacomo; Russo, Francesco Paolo; Senzolo, Marco
Summary Liver disease secondary to chronic hepatitis C virus (HCV) infection is an important cause of morbidity and mortality in patients with end‐stage renal disease (ESRD) on renal replacement therapy and after kidney transplantation (KT). Hemodialytic treatment (HD) for ESRD constitutes a risk factor for bloodborne infections because of prolonged vascular access and the potential for exposure to infected patients and contaminated equipment. Evaluation of HCV‐positive/ESRD and HCV‐positive/KT patients is warranted to determine the stage of disease and the appropriateness of antiviral therapy, despite such treatment is challenging especially due to tolerability issues. Antiviral treatment with interferon (IFN) is contraindicated after transplantation due to the risk of rejection, and therefore, treatment is recommended before KT. Newer treatment strategies of direct‐acting antiviral agents in combination are revolutionizing HCV therapy, as a result of encouraging outcomes streaming from recent studies which report increased sustained viral response, low or no resistance, and good safety profiles, including preservation of renal function. KT has been demonstrated to yield better outcomes with respect to remaining on HD although survival after KT is penalized by the presence of HCV infection with respect to HCV‐negative transplant recipients. Therefore, an appropriate, comprehensive, easily applicable set of clinical practice management guidelines is necessary in both ESRD and KT patients with HCV infection and HCV‐related liver disease.